Monitoring Indoor Air Quality Using Low-Cost IoT - Mohanad Mahmood; Kamal Y. Kamal; Saif S. Hussein (Journal of Techniques, 2025)
Measuring air quality in some regions under non-ideal circumstances is still a challenge. In many third-world countries, acquiring expensive air quality testing equipment is beyond capacity. Monitoring non-healthy environments in such regions is vital, so we implemented a low-cost IoT indoor air quality tester. The system comprises attached field instrument sensors and a WiFi-to-cloud monitoring unit. The sensing unit includes Arduino UNO attached to MQ-7, CCS811, and MQ-137 sensors to measure carbon monoxide (CO), carbon dioxide (CO2), and the total volatile organic compounds (TVOCs), and NH3, respectively. The sensors also include the DHT11 to measure temperature (T) and relative humidity (RH). To collect data from distributed field sensing devices and monitor it on the ThingSpeak website, an NRF24l01+ wireless model is connected to each data logger and the central data collector ESP32. The proposed low-cost system was operated in one of the higher education buildings of the Middle Technical University, measuring the concentrations of the most common air quality factors (CO, CO2, NH3, TVOC, RH, and T).